CUGC for posterior polymorphous corneal dystrophy (PPCD) - Davidson, Alice E; Hafford-Tear, Nathaniel J; Dudakova, Lubica; Sadan, Amanda N; Pontikos, Nikolas; Hardcastle, Alison J; Tuft, Stephen J; Liskova, Petra (European journal of human genetics, 2020)
Name of the disease (synonyms) CUGC for posterior polymorphous corneal dystrophy (PPCD).OMIM# of the disease 122000; 609141; 618031.Name of the analysed genes or DNA/chromosome segments OVOL2 (PPCD1); ZEB1 (PPCD3); GRHL2 (PPCD4).OMIM# of the gene(s) 616441; 189909; 608576. Review of the analytical and clinical validity as well as of the clinical utility of DNA-based testing for variants in theOVOL2, ZEB1andGRHL2gene(s) in a diagnostic setting, predictive and parental settings and for risk assesment in relatives.
Keywords: senzitivita a specificita; Corneal Dystrophies, Hereditary; Genetic Testing; Zinc Finger E-box-Binding Homeobox 1; transkripční faktor Zeb1; lidé; Practice Guidelines as Topic; dědičné dystrofie rohovky; DNA vazebné proteiny; Transcription Factors; transkripční faktory; Humans; genetické testování; směrnice pro lékařskou praxi jako téma; DNA-Binding Proteins; Sensitivity and Specificity